Soybean Seeds (Glycine max L.) Extract Against Cytokine Storm in ARDS Rat Model through Inhibiting Inflammation Marker - Didik Priyandoko; Wahyu Widowati; Ervi Afifah; Ika Adhani Sholihah; Cintani Dewi Wahyuni; Cahyaning Riski Wijayanti; Rizal Rizal (Bogor Agricultural University, Indonesia, 2023)
Several studies have suggested that